2017
DOI: 10.5194/amt-10-565-2017
|View full text |Cite
|
Sign up to set email alerts
|

A new zenith-looking narrow-band radiometer-based system (ZEN) for dust aerosol optical depth monitoring

Abstract: Abstract.A new zenith-looking narrow-band radiometer based system (ZEN), conceived for dust aerosol optical depth (AOD) monitoring, is presented in this paper. The ZEN system comprises a new radiometer (ZEN-R41) and a methodology for AOD retrieval (ZEN-LUT). ZEN-R41 has been designed to be stand alone and without moving parts, making it a low-cost and robust instrument with low maintenance, appropriate for deployment in remote and unpopulated desert areas. The ZEN-LUT method is based on the comparison of the m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…The ZEN-AOD-lookup table (LUT) method previously described in [37] was used to retrieve AOD from zenith sky measurements. This method compares the ZSR measured at four of the five ZEN-R52 nominal wavelengths (440, 500, 675 and 870 nm) with a LUT of precomputed ZSRs at these wavelengths.…”
Section: Aod Calculation Methods Description (Zen-aod-lut)mentioning
confidence: 99%
See 4 more Smart Citations
“…The ZEN-AOD-lookup table (LUT) method previously described in [37] was used to retrieve AOD from zenith sky measurements. This method compares the ZSR measured at four of the five ZEN-R52 nominal wavelengths (440, 500, 675 and 870 nm) with a LUT of precomputed ZSRs at these wavelengths.…”
Section: Aod Calculation Methods Description (Zen-aod-lut)mentioning
confidence: 99%
“…In a sensitivity study carried out by [37], the authors showed that the uncertainty of the ZEN-AOD-LUT method increases with AOD, having a standard uncertainty ranging from 0.06 for AOD 500 ≈ 0.5 to 0.15 for AOD 500 ≈ 1.0, when an instrumental uncertainty of 5% is considered.…”
Section: Aod Calculation Methods Description (Zen-aod-lut)mentioning
confidence: 99%
See 3 more Smart Citations